The Krispy Creme Donut. Sport as an instrument to transform gender relations : a case study of the FitSport programme, Western Cape. - Sedeman, Fabio Yves (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.